2007
DOI: 10.1016/j.physc.2007.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Precision photonic band structure calculation of Abrikosov periodic lattice in type-II superconductors

Abstract: We have performed a numerical solution for band structure of an Abrikosov vortex lattice in type-II superconductors forming a periodic array in two dimensions for applications of incorporating the photonic crystals concept into superconducting materials with possibilities for optical electronics. The implemented numerical method is based on the extensive numerical solution of the Ginzburg-Landau equation for calculating the parameters of the two-fluid model and obtaining the band structure from the permittivit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Subsequent work showed that neglect of the quasiparticles introduces significant errors, although a strongly temperature dependent quasiparticle scattering rate (as seen in certain cuprate superconductors 67 ) can restore some of the temperature tunability. 58 Development of dielectric contrast from an Abrikosov vortex lattice to create a photonic crystal is a novel idea first proposed by Takeda, et al 68 , and studied by Kokabi, et al, 69 and Zandi, et al 70 Magnetic vortices form a long-range ordered lattice in an ideal superconductor, creating a regular dielectric contrast between normal metal core tubes and the superconducting background. Takeda, et al assumed the cores were described by a constant permittivity, while outside it is a dissipation-less Drude metal.…”
Section: Iii5mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent work showed that neglect of the quasiparticles introduces significant errors, although a strongly temperature dependent quasiparticle scattering rate (as seen in certain cuprate superconductors 67 ) can restore some of the temperature tunability. 58 Development of dielectric contrast from an Abrikosov vortex lattice to create a photonic crystal is a novel idea first proposed by Takeda, et al 68 , and studied by Kokabi, et al, 69 and Zandi, et al 70 Magnetic vortices form a long-range ordered lattice in an ideal superconductor, creating a regular dielectric contrast between normal metal core tubes and the superconducting background. Takeda, et al assumed the cores were described by a constant permittivity, while outside it is a dissipation-less Drude metal.…”
Section: Iii5mentioning
confidence: 99%
“…Development of dielectric contrast from an Abrikosov vortex lattice to create a photonic crystal is a novel idea first proposed by Takeda et al [68], and studied by Kokabi et al [69] and Zandi et al [70]. Magnetic vortices form a longrange ordered lattice in an ideal superconductor, creating a regular dielectric contrast between normal metal core tubes and the superconducting background.…”
Section: Superconducting Photonic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation